2005
DOI: 10.1111/j.1464-5491.2005.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin pump therapy in childhood diabetes—cost implications for Primary Care Trusts

Abstract: The additional resources required to pay for insulin pump therapy for a small proportion of the diabetes population would be minimal given the potential benefits to these patients of improved control and anticipated reduction in long-term morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…In the light of the initial CSII HTA and NICE guidance, Feltbower et al (2006) 242 analysed the Yorkshire Register of Diabetes in Children and Young Adults. This showed an annual incidence of T1DM under 15 years of age of 19 per 100,000 person-years.…”
Section: Costs Of Csii Versus MDImentioning
confidence: 99%
“…In the light of the initial CSII HTA and NICE guidance, Feltbower et al (2006) 242 analysed the Yorkshire Register of Diabetes in Children and Young Adults. This showed an annual incidence of T1DM under 15 years of age of 19 per 100,000 person-years.…”
Section: Costs Of Csii Versus MDImentioning
confidence: 99%
“…n recent years, there has been a trend toward more intensive insulin regimens using multiple daily injections and pump therapy for children and young adults with type 1 diabetes (1)(2)(3). This trend should improve long-term glucose control, help avoid the chronic complications of diabetes, and, in theory, reduce mortality rates in subjects with type 1 diabetes.…”
mentioning
confidence: 99%
“…A further analysis performed by the DCCT research group in 1996 found that, on average, people on intensive therapy, as compared with those on conventional therapy, would experience an additional 7.7 yr of sight, 5.8 yr free from end‐stage renal disease and 5.6 yr free from lower extremity amputation (25). In support of the cost‐effectiveness of intensive therapy, it has been estimated that the additional costs of moving to insulin pump therapy are minimal, given the potential benefits (26). Insulin pump therapy can provide an effective way to help ensure consistent glycaemic control in children and adolescents.…”
Section: Resultsmentioning
confidence: 99%